Comparison of the Effects of Nonprotein and Protein Nitrogen on Apoptosis and Autophagy of Rumen Epithelial Cells in Goats - Kong, Zhiwei (Animals (Basel), 2020)
SIMPLE SUMMARY: Proteins provide important raw materials for the self-renewal of cells in the gastrointestinal tract. Cell self-renewal is inseparable from the coordination between apoptosis and autophagy. Previous researchers have explored whether different nitrogen sources are linked to activation or inhibition of apoptosis/autophagy. However, information on the regulatory mechanism of apoptosis and autophagy induced by different nitrogen sources among cells in the gastrointestinal tract is limited. This study attempted to compare the effects of different nitrogen sources on apoptosis and autophagy of rumen epithelial cells in goats through molecular biology techniques such as flow cytometry, transmission electron microscopy, and fluorescence microscopy. On the basis of the obtained results, we found that autophagy had a less obvious ameliorative effect on ruminal epithelial cell apoptosis after treatment with protein nitrogen than after treatment with nonprotein nitrogen. ABSTRACT: Protein nutrition is particularly important for the self-renewal processes of gastrointestinal epithelial cells. The self-renewal of cells is inseparable from the interaction between apoptosis and autophagy. However, there are few reports on the relationship between different nitrogen sources and apoptosis/autophagy. In this study, the relative protein expression of Bcl-2-associated X protein(Bax), caspase-3, and p62 was significantly higher (p < 0.05), while that of Bcl-xl, Bcl-2, Beclin1, and Microtuble-associated protein light chain 3 (LC3-II) was significantly lower (p < 0.05), in the NH(4)Cl group in comparison with the NH(4)Cl + 4-phenylbutyric acid (4PBA) group. In addition, the relative protein expression of Bax and caspase-3 was significantly higher (p < 0.05), while that of Bcl-2 and Bcl-xl was decreased significantly (p < 0.05), in the NH(4)Cl + 3-Methyladenine (3-MA) group and the methionine (Met) + 3-MA group in comparison with the NH(4)Cl group. Furthermore, the relative protein expression of Beclin1 and LC3B-II was significantly lower (p < 0.05), while that of p62 was significantly higher (p < 0.05), in the NH(4)Cl + Z-VAD-FMK group and the Met + Z-VAD-FMK group in comparison with the NH(4)Cl group. In conclusion, our results suggested that endoplasmic reticulum (ER) stress played a critical role in the crosstalk between apoptosis and autophagy induced by NH(4)Cl and Met. Autophagy had a more obvious ameliorative effect on ruminal epithelial cell apoptosis after treatment with nonprotein nitrogen than after treatment with protein nitrogen. These findings may reveal the molecular mechanism of apoptosis and autophagy induced by nonprotein nitrogen and protein nitrogen.